Introduction: Perspectives on Democracy - Ferdinand Müller-Rommel; Brigitte Geißel (Politische Vierteljahresschrift, 2020)
This article explores diverse views on both the current challenges and limits as well as the reforms and innovations of existing democracies at the beginning of the twenty-first century. First, it argues that socioeconomic inequality, new populism, new forms of communication, and globalization have stimulated a~renewal of interest in analyzing the “frontiers of democracy.” Democracies have reacted with different innovations and reforms in order to meet these challenges. The authors trace the phases of respective research from studies on singular, standalone instances to normative as well as empirical work on participatory (direct democratic and deliberative) systems. Finally, they advocate for combining the conceptual approach of defining democracy by the fulfillment of democratic values with rigorous empirical evaluation of the contributions (old and new) that institutions and procedures provide in order to fulfill these values and meet the mentioned challenges.
Keywords: 320; Democratic theory; Democratic innovation; Participatory reforms; New populism; Social media; Globalization; Deliberation; Direct democracy; Participatory systems; Demokratietheorie; Demokratische Innovation; Partizipatorische Reformen; Neuer Populismus; Soziale Medien; Globalisierung; Demokratische Innovationen; Deliberation; Direktdemokratie; Partizipative Systeme